DISTRIBUTED ARTIFICIAL INTELLIGENCE SYSTEM WITH AGENT- ORCHESTRATED ARCHITECTURE - Korablyov, М. М.; Novoseltsev, I. V.; Kobzev, I. V.; Tkachuk, O. K. (Systems and Technologies, 2025)
In modern AI systems, agents play a key role in making workflows flexible and adaptive, and their importance continues to grow. Agents are small components that perform focused tasks and exchange results through clear rules, which makes them useful for building reliable adaptive systems. This paper introduces an Agent-Orchestrated Architecture for adaptive AI systems. It consists of an Orchestrator and Domain Agents working together. The Orchestrator maintains a small plan with guarded steps, applies clear rules when inputs are missing or confidence is low, and records a per-case thread for audit. Domain Agents (models, tools, services) plug in behind stable contracts and handle specialized tasks. As a practical implementation, the architecture is demonstrated through a Melanoma Diagnostic Workflow: one agent gathers structured answers through focused questions and another provides a risk score from images. The Orchestrator combines both signals and applies two thresholds on the score to determine the next action – reassure with a reminder, request one or two follow-ups or a clearer photo, or recommend an in person exam – while logging every decision. The workflow is practical, auditable, and adjustable to local practice without adding complexity. The proposed architecture is applicable to domains where uncertainty and partial information are common, providing a structured way to keep systems safe, explainable, and adaptable. Beyond the medical domain, the approach generalizes to incident response, financial monitoring, and customer support, where adaptability is critical. The contribution lies in combining orchestration, reasoning, and observability as first – class design elements, offering a reproducible framework for building safer and regulation-ready AI systems.